2014
DOI: 10.1016/j.pain.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of presynaptic proteins and protein kinases associated with enhanced glutamate release from axonal terminals (synaptosomes) of the medial prefrontal cortex in rats with neuropathic pain

Abstract: Although nerve injury-induced long-term postsynaptic changes have been investigated, less is known regarding the molecular mechanisms within presynaptic axonal terminals. We investigated the molecular changes in presynaptic nerve terminals underlying chronic pain-induced plastic changes in the medial prefrontal cortex (mPFC). After neuropathic pain was induced by spared nerve injury (SNI) in rats, we assessed the release of the excitatory neurotransmitter glutamate by using in vitro synaptosomal preparations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 75 publications
2
38
0
Order By: Relevance
“…Studies reported that CaMKII is involved in the pain modulation in the brain [3,8,14]. Using CaMKII RNA-specific interfering RNA to treat visceral hypersensitive rats reduced the visceromotor response to graded colorectal distension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that CaMKII is involved in the pain modulation in the brain [3,8,14]. Using CaMKII RNA-specific interfering RNA to treat visceral hypersensitive rats reduced the visceromotor response to graded colorectal distension.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggest that CaMKII plays a key role in modulation at different levels of the central nervous system in many types of pain, especially in inflammatory pain, neuropathologic pain, cancer pain, visceral pain and postoperative pain [4,5,8,10,11,14,15,22]. Changes in the expression and activity of CaMKII are accompanied with increases in CaMKII inhibition and pain related behavior; using CaMKII inhibitors, silencing CaMKII gene expression, or delivery of CaMKII antagonist antennapedia-CaMKIINtide, attenuate pain related symptoms and produce analgesic effects in acute and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…These data are in agreement with previous findings showing that decreased levels of synaptophysin are accompanied by impairment in cognitive function and memory 84 and vice versa. 85 In contrast, some brain regions (such as the prefrontal cortex) display increased levels of synaptic proteins, 86 including synaptophysin, 87 following chronic painful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of these channels is driven by alterations in the activity of the protein kinase A/cAMP pathway under chronic pain states, thus contributing to the hyperexcitability and persistent firing of pyramidal neurons, which likely affect the perception of pain-like and mood-related symptoms. Neuropathic pain induced by the spared nerve injury model also leads to changes in synaptic proteins involved in mPFC plasticity (Hung et al, 2014). Specifically, spared nerve injury leads to an increase in synaptotagmin, synaptobrevin, and synaptophysin, and promoted time-dependent phosphorylation of extracellular regulated kinases 1 and 2 and CaMKII, as well as an increase in glutamate release.…”
Section: A Role Of the Mesolimbic Dopamine System In Analgesic/antinomentioning
confidence: 99%